2018
DOI: 10.1172/jci99397
|View full text |Cite
|
Sign up to set email alerts
|

Stromal epigenetic alterations drive metabolic and neuroendocrine prostate cancer reprogramming

Abstract: Prostate cancer is an androgen-dependent disease subject to interactions between the tumor epithelium and its microenvironment. Here, we found that epigenetic changes in prostatic cancer-associated fibroblasts (CAF) initiated a cascade of stromal-epithelial interactions. This facilitated lethal prostate cancer growth and development of resistance to androgen signaling deprivation therapy (ADT). We identified a Ras inhibitor, RASAL3, as epigenetically silenced in human prostatic CAF, leading to oncogenic Ras ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 57 publications
5
117
1
Order By: Relevance
“…However, alternative pathway(s) outside of AR signaling are also associated with prostate cancer. Recently, various signaling pathways, such as growth factors, cytokines, miRNA and epigenetic control, were reported to be related to progression of prostate cancer and conversion into CRPC, indicating that these signaling pathways could be novel therapeutic targets . Among these alternate pathways, in our study, we focused on orphan GPCRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, alternative pathway(s) outside of AR signaling are also associated with prostate cancer. Recently, various signaling pathways, such as growth factors, cytokines, miRNA and epigenetic control, were reported to be related to progression of prostate cancer and conversion into CRPC, indicating that these signaling pathways could be novel therapeutic targets . Among these alternate pathways, in our study, we focused on orphan GPCRs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various signaling pathways, such as growth factors, cytokines, miRNA and epigenetic control, were reported to be related to progression of prostate cancer and conversion into CRPC, indicating that these signaling pathways could be novel therapeutic targets. 3,34,35 Among these alternate pathways, in our study, we focused on orphan GPCRs. Integrative analyses of gene expression profiles of prostate cancer cell lines indicated that expression levels of the orphan GPCR, GPRC5A, are significantly related to overall survival of prostate cancer patients, suggesting that GPRC5A can be a candidate therapeutic target molecule involved in prostate cancer progression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been long known that cancer-associate fibroblasts can promote the progression and/or initiation of prostate epithelial cells via regulating extracellular matrix and growth factors. 97 Mishra et al 98 also reported that epigenetic changes in prostatic cancer-associated fibroblasts initiate stromaleepithelial interactions. This interaction facilitated tumor growth and development of resistance to ADT.…”
Section: Silencing Of Rasal3 and Glutamine Secretion In Tumor Microenmentioning
confidence: 99%
“…Intriguingly, although lactate is the most abundant nutrient provided in the TME, CAFs are also able to supply amino acids like glutamine to cancer cells. Epithelial cancer cells incorporate fibroblasts-derived glutamine replenishing their TCA cycle, as well as promoting an increase in aspartate-mediated nucleotide anabolism, the accumulation of oxidized glutathione and the activation of protein synthesis (85). Glutamine dependency as it is exploited as a carbon source for the energetic purposes and as a nitrogen source for nucleotide biosynthesis reflects the fact such amino acid is the most commonly depleted amino acid in TME (33).…”
Section: Glutamine and Other Aminoacidsmentioning
confidence: 99%